Assistance Of Toxic Friendship Students In Interpersonal Communication And Its Implications In Counseling - Zubaidah, Zubaidah; Yeni, Putri; Irman, Irman (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2022)
Toxic Friendship is a friendship relationship that makes a person feel unsupported, always blamed, belittled, or even attacked and all other bad things, all of this in interpersonal communication has an impact on students' daily lives starting from students having high anxiety, stress, stress and not confident in daily activities at school. The purpose of this service is to reduce the occurrence of toxic friendship in students through counseling services. Service or assistance is carried out in the form of cross-classes which on average experience toxic. The method in this service is PAR with 11 stages. Empirically this service can reduce the occurrence of toxic friendship in students, so that the effective life of students is not disrupted and other students are also able to reduce the spread of toxic friendship in the school environment.